Genotyping of foot‐and‐mouth disease viruses collected in Sudan between 2009 and 2018. Issue 5 (23rd February 2022) - Raouf, Yazeed A.; Wadsworth, Jemma; Bin‐Tarif, Abdelghani; Gray, Ashley R.; Habiela, Mohammed; Almutalb, Ameera A.; Yousif, Hanan; Ragab, Maysa; Alfouz, Wefag; Ahmed, Nussiba H.; Ibrahim, Inas; Hassan, Ahmed M.; et al.
Abstract: Foot‐and‐mouth disease (FMD) is widely distributed in Sudan where outbreaks occur on an annual basis especially during the winter months (December‐February). This study aimed to increase our understanding of the epidemiological patterns of FMD in Sudan and connections to neighbouring countries by characterizing the genetic sequences of FMD viruses (FMDV) collected from samples collected in 10 Sudanese states over a 10‐year period (between 2009 and 2018). FMDV was detected in 91 of the 265 samples using an antigen‐detection ELISA. Three serotypes were detected: O (46.2%), A (34.0%), and SAT 2 (19.8%). Fifty‐two of these samples were submitted for sequence analyses, generating sequences that were characterized as belonging to O/EA‐3 ( n  = 17), A/AFRICA/G‐IV ( n  = 23) and SAT 2/VII/Alx‐12 ( n  = 12) viral lineages. Phylogenetic analyses provided evidence that FMDV lineages were maintained within Sudan, and also highlighted epidemiological connections to FMD outbreaks reported in neighbouring countries in East and North Africa (such as Ethiopia and Egypt). This study motivates continued FMD surveillance in Sudan to monitor the circulating viral lineages and broader initiatives to improve our understanding of the epidemiological risks in the region.